Pengaruh Pemberian Senam Hamil Terhadap Tingkat Kecemasan Dan Kualitas Tidur Ibu Hamil Di Puskesmas Ketol Kecamatan Ketol Tahun 2023 - Nilawati Nilawati; Rados Kristian Nazara; Damai Putri Waruwu (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Pregnant women who have poor sleep quality during pregnancy have a negative impact on labor and fetal health. Pregnancy exercise is a body movement in the form of exercises with rules, systematics and special movement principles that are adapted to the condition of pregnant women, with the aim of making pregnant women mentally and physically ready to face the birthing process. The aim of the research was to determine the effect of pregnancy exercise on anxiety levels and sleep quality in pregnant women at the Pratama Salbiyana Clinic, Deli Serdang District in 2023. The results of the study showed that there was an effect of giving pregnancy exercise on changes in the anxiety level of pregnant women where there was a decrease in the value of anxiety level after administration. pregnancy exercise as indicated by a significance value of p=0.000. It is recommended that physiotherapists should participate more in promotive, preventive, curative and rehabilitative actions for pregnant women, such as providing pregnancy exercises to pregnant women.